The modern pollen-vegetation relationships of a tropical forest-savannah mosaic landscape, Ghana, West Africa. - Julier, Adele C.M.; Jardine, Phillip E.; Adu-Bredu, Stephen; Coe, Angela L.; Duah-Gyamfi, Akwasi; Fraser, Wesley T.; Lomax, Barry H.; Malhi, Yadvinder; Moore, Sam; Owusu-Afriyie, Kennedy; Gosling, William D. (Taylor & Francis, 2017)
Transitions between forest and savannah vegetation types in fossil pollen records are often poorly understood due to over-production by taxa such as Poaceae and a lack of modern pollen–vegetation studies. Here, modern pollen assemblages from within a forest–savannah transition in West Africa are presented and compared, their characteristic taxa discussed, and implications for the fossil record considered. Fifteen artificial pollen traps were deployed for 1 year, to collect pollen rain from three vegetation plots within the forest–savannah transition in Ghana. High percentages of Poaceae and Melastomataceae/Combretaceae were recorded in all three plots. Erythrophleum suaveolens characterised the forest plot, Manilkara obovata the transition plot and Terminalia the savannah plot. The results indicate that Poaceae pollen influx rates provide the best representation of the forest–savannah gradient, and that a Poaceae abundance of > 40 % should be considered as indicative of savannah-type vegetation in the fossil record.